Electroceramics in Japan XV : selected, peer reviewed papers from the 31st Electronics Division Meeting of The Ceramic Society of Japan, October 28-29, 2011, Tokyo, Japan - Electronics Division. Meeting (31st : 2011 : Tokyo, Japan); Katayama, K. (Keiichi), editor (Durnten-Zurich, Switzerland : Trans Tech Publications, 2013)
Includes bibliographical references and indexes